Designing Heteroatom‐Codoped Iron Metal–Organic Framework for Promotional Photoreduction of Carbon Dioxide to Ethylene - Guo, Fan; Li, Rui‐Xia; Yang, Sizhuo; Zhang, Xiao‐Yu; Yu, Hongjian; Urban, Jeffrey J.; Sun, Wei‐Yin (Angewandte Chemie (International ed.), 2023)
Rational engineering active sites and vantage defects of catalysts are promising but grand challenging task to enhance photoreduction CO2 to high value‐added C2 products. In this study, we designed an N,S‐codoped Fe‐based MIL‐88B catalyst with well‐defined bipyramidal hexagonal prism morphology via a facile and effective process, which was synthesized by addition of appropriate 1,2‐benzisothiazolin‐3‐one (BIT) and acetic acid to the reaction solution. Under simulated solar irradiation, the designed catalyst exhibits high C2H4 evolution yield of 17.7 μmol g−1⋅h, which has been rarely achieved in photocatalytic CO2 reduction process. The synergistic effect of Fe‐N coordinated sites and reasonable defects in the N,S‐codoped photocatalyst can accelerate the migration of photogenerated carriers, resulting in high electron density, and this in turn helps to facilitate the formation and dimerization of C−C coupling intermediates for C2H4 effectively. The integration of new active sites with beneficial defects in Fe‐MOF MIL‐88B catalysts gives enhanced photoreduction of CO2 to C2H4 under visible light. The modified structure promotes the migration and separation of the photoelectrons to produce the pivotal C−C coupling intermediate for the generation of C2H4, a result supported by in situ FT‐IR analysis.